Applying dynamic relaxation techniques to form-find and manufacture curve-crease folded panels. (September 2015) - Bhooshan, Shajay; Bhooshan, Vishu; ElSayed, Mostafa; Chandra, Suryansh; Richens, Paul; Shepherd, Paul
The research incorporated in the paper stems from the design and fabrication of a self-supporting, multi-panel installation for the Venice Biennale 2012 and operates against the backdrop of the exciting potentials that the field of curved-crease folding offers in the development of curved surfaces that can be manufactured from sheet material. The two main challenges were developing an intuitive design strategy and production of information adhering to manufacturing constraints. The essential contribution of the paper is a proposed interactive form-finding method for curve-crease geometries that could negotiate the multiple objectives of ease of use in exploratory design, and manufacturing constraints of their architectural-scale assemblies.